Nanostructured SnO2–ZnO composite gas sensors for selective detection of carbon monoxide - Chesler, Paul; Hornoiu, Cristian; Mihaiu, Susana; Vladut, Cristina; Calderon Moreno, Jose Maria; Anastasescu, Mihai; Moldovan, Carmen; Firtat, Bogdan; Brasoveanu, Costin; Muscalu, George; Stan, Ion; Gartner, Mariuca (Beilstein Journal of Nanotechnology, 2016)
A series of SnO2–ZnO composite nanostructured (thin) films with different amounts of SnO2 (from 0 to 50 wt %) was prepared and deposited on a miniaturized porous alumina transducer using the sol–gel and dip coating method. The transducer, developed by our research group, contains Au interdigital electrodes on one side and a Pt heater on the other side. The sensing films were characterized using SEM and AFM techniques. Highly toxic and flammable gases (CO, CO2, CH4, and C3H8) were tested under lab conditions (carrier gas was dry air) using a special gas sensing cell developed by our research group. The gas concentrations varied between 5 and 2000 ppm and the optimum working temperatures were in the range of 210–300 °C. It was found that the sensing performance was influenced by the amount of oxide components present in the composite material. Improved sensing performance was achieved for the ZnO (98 wt %)–SnO2 (2 wt %) composite as compared to the sensors containing only the pristine oxides. The sensor response, cross-response and recovery characteristics of the analyzed materials are reported. The high sensitivity (RS = 1.21) to low amounts of CO (5 ppm) was reported for the sensor containing a composite sensitive film with ZnO (98 wt %)–SnO2 (2 wt %). This sensor response to CO was five times higher as compared to its response to CO2, CH4, and C3H8, thus the sensor is considered to be selective for CO under these test conditions.
Keywords: composite thin film sensor; dip coating; low detection limit; miniaturized alumina transducer; selective CO detection; sol–gel